Inside the HR and Performance Black Box: how line managers use their people management discretion to influence individual first line employee performance outcomes - Hughes, Paul Allan W. (Cranfield University, 2016)
This study examines how front line managers use their discretion to influence first line employee performance outcomes while simultaneously meeting their responsibilities for HRM practice enactment. This addresses an academic literature gap as well as providing insight to aid the understanding between line managers and HR functions. The study is a holistic case study set within single function inside a commercial multinational organisation carried out with multiple levels of analysis. It is comprised of confidential primary data collection and triangulation interviews with 11 line managers from above and below average performing teams, 23 of their direct reports and 2 representatives from the HR function. Organisation documentation, reports and performance data were also examined. The study identified the discretionary practices used by line managers to influence employee performance outcomes alongside those they used for enacting their HRM practice responsibilities, while variations in discretionary practice usage between above and below average line managers helped explain differences in employee performance outcomes. Further research is needed to determine whether this is a causal relationship. The study also found new forms of HRM practice enactment carried out by front line managers extending our understanding on how this is carried out in organisations. Further variations in front line manager HRM practice enactment were not found to as related to employee performance outcome differences questioning that lack of compliance with HRM practices leads to poorer employee performance outcomes. There was limited overlap between the discretionary practices found and LMX theory suggesting a limited utility as a method for examining front line manager discretion in this context. The study also offers a practical model using CIMO-logic to help provide those in organisations better understanding between front line managers and the HRM practices they have responsibilities, with potential to build better interactions between front line managers and those in HRM functions. The findings extend our existing theory, suggesting more complex and dynamic approaches are used by some front line managers than previously thought with resultant implications for further research and practice.
Keywords: HRM-P; first line managers; first line employees; employee performance; HRM practices; people management; AMO; LMX; CIMO